Web-based interventions for pregnant women with gestational diabetes mellitus: a systematic review and meta-analysis protocol - Ping Xu; Wei Zhang; Xiaojuan Wang; Dan Dan Chen; Pingping Guo; Yin Jin; Zhenzhen Xiang; Minna Mao; Qiong Zheng; Suwen Feng (BMJ Open)
Introduction Gestational diabetes mellitus (GDM) is one of the most prevalent diseases during pregnancy, which is closely associated with many short-term and long-term maternal and neonatal complications and can incur heavy financial burden on both families and society. Web-based interventions have been used to manage GDM because of the advantages of high accessibility and flexibility, but their effectiveness has remained inconclusive. This systematic review and meta-analysis aims to comprehensively investigate the multidimensional effectiveness of web-based interventions for pregnant women with GDM, thereby aiding implementation decisions in clinical settings.Methods and analysis This systematic review protocol strictly adheres to the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guidelines. Six electronic databases (PubMed, Web of Science, Cochrane Central Register of Controlled Trials, Embase, CINAHL and PsycINFO) will be comprehensively searched from their inception to 26 January 2022 to identify randomised controlled trials and controlled clinical trials regarding the efficacy of web-based interventions for pregnant women with GDM on glycaemic control, behavioural outcomes, cognitive and attitudinal outcomes, mental health, maternal and neonatal clinical outcomes, and medical service utilisation and costs. Two reviewers will independently conduct the study selection, data extraction and quality assessment. The methodological quality of included studies will be assessed using the Effective Public Health Practice Project assessment tool. The overall meta-analyses for each of the interested outcomes will be performed if the outcome data are sufficient and provides similar effect measures, as well as subgroup analyses for glycaemic control indicators based on the different types of intervention format, interactivity and technology. We will conduct a qualitative synthesis for studies that cannot be quantitatively synthesised.Ethics and dissemination Ethics approval is not required for this review as no human participants will be involved. The results will be disseminated via a peer-reviewed journal or an academic conference.PROSPERO registration number CRD42022296625.